2012
DOI: 10.1002/brb3.88
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment: effect of education on the verbal and nonverbal tasks performance decline

Abstract: We sought to longitudinally evaluate the potential association of educational level with performance on verbal and nonverbal tasks in individuals with mild cognitive impairment (MCI). We evaluated patients with MCI, age >50 years, no medication intake, absent vascular risk factors, and no lesions on brain magnetic resonance imaging (MRI). Each patient underwent a clinical assessment packet and a series of neuropsychological tests of the language and constructional praxis subtests of Cambridge Cognitive Examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…[ 12 ] Higher level of education appears to be not only protective of cognitive function but also seems to be associated with slower deterioration over a longitudinal course in patients with severe cognitive impairment such as dementia, suggestive of underlying cognitive reserve phenomena that are operating. [ 38 39 ] Similarly, an inverse association of age with cognitive function in alcohol dependence has been reported, as observed in this study. [ 12 ] With aging, there is difficulty in the speed of information processing and transforming information to make decisions and difficulty in executive functioning that may be aggravated by alcohol dependence.…”
Section: Discussionsupporting
confidence: 85%
“…[ 12 ] Higher level of education appears to be not only protective of cognitive function but also seems to be associated with slower deterioration over a longitudinal course in patients with severe cognitive impairment such as dementia, suggestive of underlying cognitive reserve phenomena that are operating. [ 38 39 ] Similarly, an inverse association of age with cognitive function in alcohol dependence has been reported, as observed in this study. [ 12 ] With aging, there is difficulty in the speed of information processing and transforming information to make decisions and difficulty in executive functioning that may be aggravated by alcohol dependence.…”
Section: Discussionsupporting
confidence: 85%
“… 33 In addition, memory and language functions were found to be more resistant to decline in the high-education group. 17 Evidence indicated that higher education can attenuate the negative effect of TBI on cognitive outcomes. 34 Educated patient status proved an independent predictor of 1-year disability-free recovery even after traumatic brain injury was adjusted for other prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…While higher educated patients may be more acquainted with the tasks, slower deterioration in consecutive follow-up examinations could be explained by the cognitive reserve theory. 17 …”
mentioning
confidence: 99%
“…The existing relevant data in Greece stems only from retrospective FTD [18] or early dementia patient series [19], an outdated AD prevalence study [20], and a prospective study on the effects of education in cognitive decline among MCI subjects [21]. This study is also one of the largest in the relevant international literature, including both bvFTD and PPA patients.…”
Section: Discussionmentioning
confidence: 99%